Evaluation of waste polyethylene terephalate in polyol and polyurethane production - Firat, Tulay; Kar, Filiz (Sage Publications Inc, 2023)
As technology advances and human population grows, we must meet our diverse needs while minimising harm to the environment. One solution is to prioritise recycling and using second-hand consumer goods. In this study, PET flakes were depolymerised by glycolysis using different molar ratios of glycol such as propylene glycol(PG), triethylene glycol(TEG) and polyethylene glycol(PEG 400) in the presence of two different catalysts: zinc acetate- zinc sulphate. As a result, glycated products (polyols-PO) were obtained. The obtained polyols were then used to synthesise polyurethane films (PU) via acetone process. The thermal and chemical characterisations of the polyurethane films (PU) were analysed. In similar studies, zinc acetate was used as a transesterification catalyst for the glycolysis process. In this study, the same process was carried out using zinc sulphate and zinc acetate. Zinc sulphate was found to be a cheaper and eco-friendlier catalyst alternative to zinc acetate for the glycolysis process.
Keywords: PET waste; glycolysis; polyol; polyurethane; degradation